The sour grape [book with audioplayer] - John, Jory (John, Jory. Food group., 2023)
"The Sour Grape holds grudges for every reason under the sun. Lime never returned a scarf they borrowed? Grudge! Orange never called back? Grudge! But when a friend holds a grudge against the Sour Grape without listening to an explanation, the Sour Grape realizes how unfair grudges can be. Could a bunch of forgiveness and compassion be enough to turn a sour grape sweet?"-- Amazon.